2008
DOI: 10.1007/s11192-008-0429-8
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the connection between researchers’ productivity and their co-authors’ past attributions, including the importance in collaboration networks

Abstract: Although many studies have analyzed the "synchronic" correlation of properties between authors and their co-authors, the "diachronic" correlation of properties, i.e., the correlation between their subsequent and precedent activity, has not yet been sufficiently studied using quantitative methods. This study pays attention not only to productivity but also the importance in the collaboration network as a measure of the researcher's activity, and clarifies whether there is any connection between (i) the research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 18 publications
0
19
1
3
Order By: Relevance
“…Next, we disambiguated names in the same dataset by using the first and all initial disambiguation methods, and generated a network from each dataset. We excluded the hybrid method from our analysis because it has not been frequently used except in one empirical study by Yoshikane et al (2009). For the first and all initial disambiguation methods, some preprocessing is required.…”
Section: Generating Coauthorship Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we disambiguated names in the same dataset by using the first and all initial disambiguation methods, and generated a network from each dataset. We excluded the hybrid method from our analysis because it has not been frequently used except in one empirical study by Yoshikane et al (2009). For the first and all initial disambiguation methods, some preprocessing is required.…”
Section: Generating Coauthorship Networkmentioning
confidence: 99%
“…Only one paper disambiguated with the hybrid method (Yoshikane, Nozawa, Shibui, & Suzuki, 2009). Some scholars just indicated that an initial based disambiguation had been performed without details on the strategy (6 papers, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…É importante ressaltar que, devido aos valores dos coeficientes de determinação nas regressões serem baixos, há a possibilidade de outros fatores, como convergência de pensamento, afinidade pessoal, afinidade metodológica e teórica explicarem a produtividade de pesquisadores (Yoshikane et al, 2009). …”
Section: Discussionunclassified
“…16 In some cases, productivity, networks and research activities occur prior to the start of collaboration. 17 Although there is a large reserve of empirical studies on scientific networks, theoretical models that explain them are rather inadequate. 18 The network formation game is an exception.…”
mentioning
confidence: 99%